Formoterol fumarate + glycopyrrolate for the treatment of chronic obstructive pulmonary disease. (2nd October 2016) - Radovanovic, Dejan; Mantero, Marco; Sferrazza Papa, Giuseppe Francesco; Valenti, Vincenzo; Aliberti, Stefano; Di Marco, Fabiano; Santus, Pierachille
ABSTRACT: Introduction : Chronic obstructive pulmonary disease (COPD) is characterized by a high disability and increasing mortality. Bronchodilators are the cornerstone of pharmacological treatment in COPD, while therapeutic optimization with an improvement in symptoms and compliance represent the actual goals. This has led to the development of devices that combine different classes of inhalatory drugs. Recently, a novel combination of the long acting antimuscarinic agent glycopyrronium bromide and the beta2-agonist formoterol fumarate has been developed in a metered dose inhaler delivery system. Areas covered : The present article will discuss the current unmet needs in pharmacological therapy of COPD, will then briefly cover the pharmacokinetic and pharmacodynamic characteristics of the formoterol/glycopyrronium fixed dose combination and present the novel delivery system based on engineered microparticles and the co-suspension technology. Finally, efficacy and safety results of phase I, II and III trials will be reviewed. Expert commentary : The novel combination therapy of formoterol/glycopyrronium is the first available as a metered dose inhaler and proved to have a good efficacy and safety profile compared to monocomponents and tiotropium. Although still limited, data from phase III trials provide good evidence to consider it a valid option in the pharmacological management of patients with COPD.